Child Health Surveillance: nurses perspective - Yakuwa, Marina Sayuri; Silva Sartori, Mariana Claudio da; Mello, Debora Falleiros de; Cassamassimo Duarte, Marli Teresinha [UNESP]; Pamplona Tonete, Vera Lucia [UNESP] (Assoc Brasileira Enfermagem, 2015)
Objective: to analyze conceptions of nurses on child health surveillance in family health units. Method: a qualitative study with thematic analysis of the data, based on the paradigm of Health Surveillance. Interviews were conducted with 13 nurses in a countryside city in the state of Sao Paulo. Results: nurses conceived child health surveillance as an active monitoring, which should be comprehensive, identifying risks/vulnerabilities, through multidisciplinary and intersectoral actions that are dependent on maternal involvement. We found partial development of these assumptions in practice, due to difficulties such as lack of maternal involvement in the proposed actions, lack of time for discussion and adoption of measures in the units and disarticulation between levels and sectors of the city. Conclusion: a greater political and technical investment is needed to ensure the adoption of this model in different sectors and levels of care of the city.
Keywords: Surveillance; Children's Health; Family Health Strategy; Nursing